Dietary Patterns and Type 2 Diabetes: A Systematic Literature Review and Meta-Analysis of Prospective Studies - Jannasch, Franziska; Kröger, Janine; Schulze, Matthias B (The Journal of nutrition, 2017)
Different methodologic approaches for constructing dietary patterns and differences in their composition limit conclusions on healthful patterns for diabetes prevention. We summarized evidence from prospective studies that examined associations of dietary patterns with type 2 diabetes by considering different methodologic approaches. The literature search (MEDLINE and Web of Science) identified prospective studies (cohorts or trials) that associated dietary patterns with diabetes incidence in nondiabetic and apparently healthy participants. We summarized evidence by meta-analyses and distinguished different methodologic approaches. The search resulted in 48 articles comprising 16 cohorts. Adherence to the Mediterranean diet (RR for comparing extreme quantiles: 0.87; 95% CI: 0.82, 0.93), Dietary Approaches to Stop Hypertension (DASH) (RR: 0.81; 95% CI: 0.72, 0.92), and Alternative Healthy Eating Index (AHEI) (RR: 0.79; 95% CI: 0.69, 0.90) was associated with significant risk reductions of incident diabetes. Patterns from exploratory factor and principal component analyses characterized by red and processed meat, refined grains, high-fat dairy, eggs, and fried products ("mainly unhealthy") were positively associated with diabetes (RR: 1.44; 95% CI: 1.27, 1.62), whereas patterns characterized by vegetables, legumes, fruits, poultry, and fish ("mainly healthy") were inversely associated with diabetes (RR: 0.84; 95% CI: 0.77, 0.91). Reduced rank regression (RRR) used diabetes-related biomarkers to identify patterns. These patterns were characterized by high intakes of refined grains, sugar-sweetened soft drinks, and processed meat and were all significantly associated with diabetes risk. Our meta-analysis suggests that diets according to the Mediterranean diet, DASH, and AHEI have a strong potential for preventing diabetes, although they differ in some particular components. Exploratory dietary patterns were grouped based on concordant food groups and were significantly associated with diabetes risk despite single-component foods having limited evidence for an association. Still, they remain population-specific observations. Consistent positive associations with diabetes risk were observed for 3 RRR patterns.